Assessing the Process Not Just the Message: A Cursory View of Student Assessment - Amalia, Liza; Bustos, Jacki (International Journal of Culture and Art Studies, 2018)
Knowing the tremendous importance of the grade, we spent several weeks discussing, researching, and writing about the process of assessing student work. As we evaluated the written work of Claire Evelyn, an eighteen-year-old, second-semester freshman enrolled in ENGL 112, Composition and Literature, at a regional campus in Ohio, we were able to balance the enormous weight of assessing Evelyn’s work with the growing confidence in our skills. Our confidence stemmed from reading, understanding, and applying the composition theory found in our collaborative research. The particular assignment that we are assessing includes a unit of writing comprised of a final portfolio, dialogue journal, and Evelyn’s reflective letter. We will discuss the general justification and reasoning of our assessment based on the theory of process grading, rubrics, and of course, Evelyn’s written text. After some deliberation and through the use of the rubric we established, we settled on a C+ for Claire. As we began this research, our initial reaction was to grade the final draft without taking into account the other materials. Upon further discussion and research, we collectively decided to broaden our scope and include the reflection journal and the dialogue letters. By extending the text beyond one draft, we were able to give her a grade more fitting for the scope of her writing.